2014
DOI: 10.1007/s12603-014-0474-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of caffeine ingestion on functional performance in older adults

Abstract: Caffeine is a widely used nutritional supplement which has been shown to enhance both physical and cognitive performance in younger adults.However, few studies have assessed the effect of caffeine ingestion on performance, particularly functional performance in older adults. The present study aims to assess the effect of acute caffeine ingestion on functional performance, manual dexterity and readiness to invest effort in older adults.Methods: 19 apparently healthy, volunteers (10 females and 9 males aged 61-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 38 publications
3
19
2
Order By: Relevance
“…As there was no change in performance during the repeated contraction protocol of the elbow flexors, it was unsurprising that perception of pain was not affected by the caffeine treatment. The improved performance of the knee extensors during repeated contractions, coincides with the growing body of evidence that demonstrates a caffeine induced increase in performance without notable modulation of pain perception (Tallis, Duncan et al 2013;Duncan et al 2014;Tallis, Muhammad et al 2016). As such, the given improvement in muscle performance demonstrated in the present study is likely to relate to the action of caffeine as a D r a f t CNS stimulant (Nehlig et al 1992) and (or) its ability to act directly on skeletal muscle (Tallis, Duncan et al 2015).…”
Section: Effect Of Caffeine On Pain Perceptionsupporting
confidence: 83%
“…As there was no change in performance during the repeated contraction protocol of the elbow flexors, it was unsurprising that perception of pain was not affected by the caffeine treatment. The improved performance of the knee extensors during repeated contractions, coincides with the growing body of evidence that demonstrates a caffeine induced increase in performance without notable modulation of pain perception (Tallis, Duncan et al 2013;Duncan et al 2014;Tallis, Muhammad et al 2016). As such, the given improvement in muscle performance demonstrated in the present study is likely to relate to the action of caffeine as a D r a f t CNS stimulant (Nehlig et al 1992) and (or) its ability to act directly on skeletal muscle (Tallis, Duncan et al 2015).…”
Section: Effect Of Caffeine On Pain Perceptionsupporting
confidence: 83%
“…Furthermore, it has been suggested that caffeine has a greater ergogenic benefit in non‐habituated consumers (Bell and McLellan, ). Caffeine is rich in the Western diet and it is almost impossible to recruit participants who consume similar quantities of caffeine, and in many studies participants are considered to be habitual users (Tarnopolsky and Cupido, ; Bridge and Jones, ; Duncan et al ., ). Although the effects of habituation to caffeine on the magnitude of the response to a particular dose of caffeine need to be investigated further (Graham, ; Astorino and Roberson, ), this could be why there are responders and non‐responders to caffeine treatment, as reported in studies examining responses at an individual level (Skinner et al ., ).…”
Section: Caffeine and Sports Performancementioning
confidence: 97%
“…Another methodological debate relates to the withdrawal of caffeine before completion of the experimental trial. It is common practice for researchers to restrict caffeine consumption 12–48 h before completion of the exercise protocol (Bell and McLellan, ; Glaister et al ., ; Duncan et al ., ). Although there is evidence indicating that withdrawal has limited effects on exercise performance, there is a wealth of literature demonstrating its negative effects on mood, stress, fatigue, alertness and short‐term memory (Smith, ).…”
Section: Caffeine and Sports Performancementioning
confidence: 97%
See 1 more Smart Citation
“…Whilst we might typically focus on the ergogenic effects of caffeine in younger participants, caffeine’s performance-enhancing effects may hold promise as a method of acutely enhancing exercise capacity, performance, and activities of daily living in older adults. Research has demonstrated that caffeine is effective in enhancing exercise performance in older adults [ 124 , 182 ]; however, there is the possibility that the magnitude of ergogenic effects varies with age.…”
Section: What Else Do We Need To Know About Caffeine In Sport?mentioning
confidence: 99%